(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Proverbs and Sayings – is the property of the people who created by the centuries under the ancient society, when there was no means of the material thought. Proverbs and Sayings is a genre of folklore, aphoristic concise, imaginative, grammatically and logically complete utterance instructive sense of rhythm organized form. Proverb is property of the whole people, or a large part of it, and contains a general judgment or counsel on any occasion. Proverb – the most interesting genre of folklore. The fruits of centuries-old observation and reflection of the people, his hopes and dreams embodied in songs, fairy tales. So people had been creating his art, his poetry. Proverb lives in speech, but only capacious proverb acquires its specific meaning.